Antimicrobial activity of crude extracts and fractions of Vernonia polyanthes Less (assa-peixe) flowers - K.K. WALTRICH; J. HOSCHEID; I.S. PROCHNAU (Universidade Estadual Paulista, 2015)
ABSTRACT Vernonia polyanthes, known as "assa-peixe", is a plant native to Brazil, and the decoction or infusion of its flowers, roots and leaves are used in folk medicine, being considered sources of diuretic, balsamic, anti-rheumatic substances, and are used in cases of bronchitis and persistent cough. The aim of the study was to evaluate the antimicrobial activity of the extract/fractions obtained by methanol maceration and infusion of V. polyanthes flower, also including qualitative identification of flower compounds, through phytochemical evaluation, using colorimetric tests. Identification tests for the presence of anthraquinones, tannins, flavonoids, saponins and alkaloids were performed. Microbiological evaluation was made through agar diffusion assay, using Escherichia coli, Staphylococcus aureus and Pseudomonasaeruginosa as test organisms. From the performed colorimetric tests it was possible to verify the presence of tannins and flavonoids in both extracts. Alkaloids were also observed in the macerated extract. The ethyl acetate fraction from the agar diffusion assay, from both extracts, presented microbial activity over Staphylococcus aureus. It was possible to qualitatively identify the floral compounds, and to show the differences between extraction methods, being methanol considered the best solvent to the extraction.